1981
DOI: 10.1002/pssa.2210680123
|View full text |Cite
|
Sign up to set email alerts
|

On the use of powder diffractometry in the study of phase transitions case of NaNO2

Abstract: The phase transition of NaNO2, is investigated by using X‐ray powder diffractometry. The temperature dependence of the lattice constants, peak intensities, and the order parameter of the ferroelectric phase, in the range of 27 to 200 °C, show the same results as obtained by using single‐crystal diffractometry. These experimental findings imply that the X‐ray powder method is suitable for the study of phase transition. The analysis of the powder diffraction profile would even improve the method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0
5

Year Published

1985
1985
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 13 publications
0
6
0
5
Order By: Relevance
“…This value of β is in a good agreement with the value (0.362±0.004) obtained for the 3D-Ising model [20], by computer simulation of finite-size scaling for a second order PT. The curve η(T) for CFM for the 20 nm porous glass differs principally from those for nanocomposites with 3 and 7 nm pores and looks similar to the dependence obtained for the bulk [19]. Keeping in mind the results of the dielectric study of sodium nitrite within opal [7], where two types of nanocaverns exist with characteristic sizes from 70 nm up to 120 nm (and in which the authors observed a temperature hysteresis of the dielectric permittivity), and our results for the size of nanoparticles and their temperature dependence of the order parameter, one can conclude that at nanoparticle sizes smaller than 50 nm a crossover from a first order PT to a second order one takes place.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…This value of β is in a good agreement with the value (0.362±0.004) obtained for the 3D-Ising model [20], by computer simulation of finite-size scaling for a second order PT. The curve η(T) for CFM for the 20 nm porous glass differs principally from those for nanocomposites with 3 and 7 nm pores and looks similar to the dependence obtained for the bulk [19]. Keeping in mind the results of the dielectric study of sodium nitrite within opal [7], where two types of nanocaverns exist with characteristic sizes from 70 nm up to 120 nm (and in which the authors observed a temperature hysteresis of the dielectric permittivity), and our results for the size of nanoparticles and their temperature dependence of the order parameter, one can conclude that at nanoparticle sizes smaller than 50 nm a crossover from a first order PT to a second order one takes place.…”
Section: Resultsmentioning
confidence: 56%
“…It is known [19] that the dependence of the intensity of diffraction peaks on the structure factor for sodium nitrite can be written in the following form…”
Section: Resultsmentioning
confidence: 99%
“…На вставке показаны температурные зависимости интегральной интенсивности, нормированной на значение при комнатной температуре, пиков (022) (кружки) и (121) (квадраты). Температурные зависимости параметра порядка η(T ) чистого NaNO 2[14] (сплошная линия) и композита с x = 0.1 (точки, штриховая линия -результат процедуры сглаживания). На вставке приведены значения η(T ) при нагреве (темные кружки, сплошная линия) и охлаждении (светлые кружки) для композита.…”
unclassified
“…1 Introduction Sodium nitrite, NaNO 2 , which is a ferroelectric material [1], undergoes an order-disorder phase transition at about 436.2 K [2]. Below this temperature, the structure of NaNO 2 is orthorhombic and is polar along the b-axis with space group 20 2v C -Immm [3], and it is in the ferroelectric phase.…”
mentioning
confidence: 99%
“…We have also calculated the Brillouin frequencies close to the phase transition in NaNO 2 [51,52] using the experimental data for the thermal expansivity [15] and compared them with the experimental Brillouin frequencies [30]. Our calculation for the spontaneous polarization using the mean field theory [53] has been compared with the experimental data [2] for NaNO 2 in the ferroelectric phase. We have also studied the spectroscopic modifications of the Pippard relations for NaNO 2 in the paraelectric phase [54] and antiferroelectric phase with sinusoidal modulation of electric dipole moments [55].…”
mentioning
confidence: 99%